Introduction to “Discourse, Metaphysics, and Hermeneutics of the Self” by Paul Ricoeur - Samuel Lelièvre (Études Ricoeuriennes / Ricoeur Studies)
When examining the relationship of Ricoeur’s philosophy to the field of ontology and metaphysics, a text entitled “Discourse, metaphysics and the hermeneutics of the self” may attract attention as it provides useful and meaningful insights. This text is a reworking of a better-known text, “De la métaphysique à la morale” (1993), but remains different by focusing on analyses relating to an ontology and metaphysics of human action and agency, and considers the speculative structure of a hermeneutics of the self constituted since Oneself as Another (1990). Originating from a conference held at the Universidade de Santiago de Compostela (Spain) in 1993 and 1995, this text was first published in 1998 in the proceedings of that conference; the present version aims at making it accessible again and improving its editorial form.